Targeting the Urokinase-Type Plasminogen Activator Receptor (uPAR) in Human Diseases With a View to Non-invasive Imaging and Therapeutic Intervention - Leth, Julie Maja; Ploug, Michael (Frontiers in Cell and Developmental Biology, 2021)
The interaction between the serine protease urokinase-type plasminogen activator (uPA) and its glycolipid-anchored receptor (uPAR) focalizes plasminogen activation to cell surfaces, thereby regulating extravascular fibrinolysis, cell adhesion and migration. uPAR belongs to the Ly6/uPAR (LU) gene superfamily and the high-affinity binding site for uPA is assembled by a dynamic association of its three consecutive LU domains. In most human solid cancers, uPAR is expressed at the invasive areas of the tumor-stromal microenvironment. High levels of uPAR in resected tumors or shed to the plasma of cancer patients are robustly associated with poor prognosis and increased risk of relapse and metastasis. Over the years, a plethora of different strategies to inhibit uPA and uPAR function have been designed and investigated in vitro and in vivo in mouse models, but so far none have been implemented in the clinics. In recent years, uPAR-targeting with the intent of cytotoxic eradication of uPAR-expressing cells have nonetheless gained increasing momentum. Another avenue that is currently being explored is non-invasive imaging with specific uPAR-targeted reporter-molecules containing positron emitting radionuclides or near-infrared (NIR) florescence probes with the overarching aim of being able to (i) localize disease dissemination using positron emission tomography (PET) and (ii) assist fluorescence guided surgery using optical imaging. In this review, we will discuss these advancements with special emphasis on applications using a small 9-mer peptide antagonist that targets uPAR with high affinity.